FINANÇAS DESCENTRALIZADAS (DeFi), BLOCKCHAIN E DESAFIOS TRIBUTÁRIOS - PERÔNICO, FRANCINALDO GOMES (2022)
Virtual financial transactions are currently on the rise and have brought unexpected changes to the already established financial and tax system. Blockchain is a current technological system that performs transactions in a decentralized way, being managed by third parties. Decentralized finance (DeFi) is built on the blockchain, they also aim to decentralize and disintermediate cryptocurrency financial services. Cryptocurrencies are current virtual financial assets that have their values established, having some difficulty in the economic taxation of these goods in view of the fact that they are not really considered currencies by the institutions of law. In this north, it can be seen that the norms and tax regulations may still fall short of current technological changes. Thus, this study intends to launch a critical view, from the point of view of the tax law, on the subject and highlight the gaps, legal and technological challenges that will be faced, respectively, by the legislator and the tax authority when regulating the matter. and in a specific way. In short, from the analysis made about Decentralized Finance (DeFi), blockchain and cryptocurrencies, the exponential growth of these technologies is denoted, they intend to offer their users and investors lower expenses in transactions, greater ease and practicality, as well as privacy about your virtual assets. Despite the above, the lack of formalities specified by law can be seen, these digital goods are not yet part of specific regulations that oblige them to pay income tax. However, it is reiterated that due taxation is feasible for these technologies, smart contracts and the blockchain network guarantee through a coding system the verification of violations and the entire negotiation process between the parties, while guaranteeing privacy to users. Thus, it is necessary that the legislature regulates these virtual assets in a specific law and guarantees the state of law the due taxation.